Ayurvedic Management of Manyastambha (Cervical Spondylosis) w.s.r. to Therapeutic Role of Mashbaladi Kwatha Nasya - Kumar, Yogesh; Bhatkoti, Mayank; Panwar, Balkrishan; Kumar, Vipin (International Research Journal of Ayurveda & Yoga, 2022)
Manyastambha is Vataja nanatmaja vyadhi due vata prakopaka nidana sevana. The vata dosha gets vitiated and lodges in manya causing stambha and ruja of the neck that ultimately led to manyastambha. manyastambha can be more or less studied under broad heading of cervical spondylosis as both of these are having similar signs and symptoms. Cervical spondylosis is a degenerative condition of the cervical spine it is age related condition that affects the neck vertebra. The disease not only negatively impacts a person’s health but also greatly impairs quality of life and daily activities. The treatment of Manyastambha, were proposed for prevention and control by ayurveda. In ayurveda there are very treatment modalities, among them nasya has been given much importance role in Uurdhvajatrugata roga. Acharya charka has indicated nnasya therapy exclusively for the management of Manyastambha. The current article discusses the function of particular ayurvedic methods in the treatment of Manyastambha(cervical spondylosis).